Development of Textbook: Mental Health Flipbook for Guidance and Counselling Student in Higher Education - Puriani, Risma Anita; Dewi, Ratna Sari; Lubis, Khadijah; Marlini, Leny; Pratama, Nanda Putra (Kuras Institute, 2025)
Textbooks are one of the media specifically designed to assist the learning process in a particular subject area. Textbooks have an important function, books that are used as handbooks for courses compiled and written by experts in their fields. Through textbooks, students are expected to be able to obtain information and various activity instructions in learning in each course. This study aims to develop Flipbook Teaching Materials in Mental Health Courses for Guidance and Counselling students of FKIP Sriwijaya University. Measurements in this study on the main data, namely the results of coursebook assessments on media validation, material validation, and language validation, as well as the results of the flipbook feasibility test by measuring student absorption of the material in the coursebook. This research uses the ADDIE development method with a series of Analysis, Design, Development, Implementation and Evaluation. the instruments in this study were expert validation sheets and respondent rating scales. The results showed media validation with a total average of 4.43 with the category